Análise da integração interfuncional no processo de entrega de valor: estudo das estratégias integradas de demanda e suprimento em uma indústria de bens de consumo rápido - Quinaglia, Eric Alberto (2019)
Demand and supply processes are of great importance for cross-functional integration, as they connect their activities directly to organizational strategies with a focus on balancing operational efficiencies and delivering value to customers. The aim of this study is to identify and analyze how the cross-functional integration of demand and supply strategies contribute to customer value delivery in the context of the fast-moving consumer goods industry. The study used the systematic approach with bibliometric analysis on four indexing platforms to compose the development of the theoretical review. This research has a qualitative and exploratory objective, in which it used a single case study to collect and analyze the results investigated in the main strategies present in the demand and supply processes in a national large beverage company. The results presented explore the dynamics of integration against the six most important strategies, according to the investigated company's experts, which are essential for the integration of demand and supply processes, describing, in each of them, their contact points, integration factors and impacts generated. In addition, for a better visualization of the results, a cross analysis of the integration between demand and supply was carried out, which resulted in the formation of study propositions, which point to greater brand exposure and territorial presence, increased sales volume, agility in terms of time. delivery and greater timing and flexibility to adapt to changes and market reactions. The research has as limitation the use of the single case study as a research method, suggesting that future studies may investigate other segments and departments in more than one company to corroborate the dynamics of cross-functional integration.